2018
DOI: 10.3168/jds.2017-13774
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation and distillation of cheese whey: Carbon dioxide-equivalent emissions and water use in the production of whey spirits and white whiskey

Abstract: Whey disposal can be both an environmental and economic challenge for artisanal creameries. Lactose in whey can be fermented to produce ethanol and subsequently distilled. The objective of this study was to use a process-based life cycle analysis to compare carbon dioxide-equivalent (COe) emissions and water usage associated with the artisanal or craft production of clear, unaged spirits using whey or malted barley as fermentation substrate. Differences in production were assessed based on key process differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
(22 reference statements)
0
20
0
1
Order By: Relevance
“…One avenue includes the conversion of the lactose within whey to ethanol. The fermentation process reduces the biochemical oxygen demand by approximately 75% (Siso, 1996) and it has been illustrated on an artisanal creamery level to be environmentally advantageous (Risner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One avenue includes the conversion of the lactose within whey to ethanol. The fermentation process reduces the biochemical oxygen demand by approximately 75% (Siso, 1996) and it has been illustrated on an artisanal creamery level to be environmentally advantageous (Risner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has also illustrated that production of a spirit from whey destined to be land spread instead of a similar grain-based spirit can reduce net CO 2 -equivalent emissions [71]. This 2018 study also indicated that the production of a wheybased spirit required less water than a grain-based spirit [71]. These factors indicate that the production of a spirit from whey may be beneficial to the whey producer, distiller and the environment.…”
Section: Environmental Implications Of Whey Spirit Productionmentioning
confidence: 87%
“…K. marxianus is classified as GRAS and can be used as feed for livestock. It has also illustrated that production of a spirit from whey destined to be land spread instead of a similar grain-based spirit can reduce net CO 2 -equivalent emissions [71]. This 2018 study also indicated that the production of a wheybased spirit required less water than a grain-based spirit [71].…”
Section: Environmental Implications Of Whey Spirit Productionmentioning
confidence: 90%
See 1 more Smart Citation
“…Dairy industries, especially small‐ and medium‐sized producers of artisanal cheeses, commonly discard large volumes of whey landspreading, causing environmental contamination (Risner et al . ). Whey as an effluent is a potential pollutant due to its high biochemical oxygen demand, and its adequate disposal requires expensive treatment (Pescuma et al .…”
Section: Introductionmentioning
confidence: 97%